2011
DOI: 10.1039/c1sm05358b
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-mediated interactions between circular particles in the strongly curved regime

Abstract: Particles binding to a fluid lipid membrane can induce bilayer deformations, for instance when these particles are curved. Since the energy of two overlapping warp fields depends on the mutual distance between the two particles creating them, they will experience forces mediated by the curvature of the membrane. If the deformations are sufficiently weak, the associated differential equations for the membrane shape are linear, and the resulting interactions are understood very well; but very little is known for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 37 publications
6
95
3
Order By: Relevance
“…Compared to the scale of the plasma membrane which can be approximately considered as a flat surface, the curved nature of such a tubular membrane can significantly affect these interactions. Recently, it has been revealed that hard particles and semiflexible polymers absorbed to soft elastic shells, collectively induce aggregates and produce a rich variety of aggregation patterns [18,[20][21][22][23][24][25][26]. Particularly, Pàmies and Cacciuto showed that spherical nanoparticles adhering to the outer surface of an elastic nanotube can selfassemble into diverse aggregates [22].…”
mentioning
confidence: 99%
“…Compared to the scale of the plasma membrane which can be approximately considered as a flat surface, the curved nature of such a tubular membrane can significantly affect these interactions. Recently, it has been revealed that hard particles and semiflexible polymers absorbed to soft elastic shells, collectively induce aggregates and produce a rich variety of aggregation patterns [18,[20][21][22][23][24][25][26]. Particularly, Pàmies and Cacciuto showed that spherical nanoparticles adhering to the outer surface of an elastic nanotube can selfassemble into diverse aggregates [22].…”
mentioning
confidence: 99%
“…This principle has been successfully used to predict the interactions of membraneembedded proteins and nanoparticles (11)(12)(13). However, in the case of nuclear envelope, Fig.…”
mentioning
confidence: 99%
“…(3) and modifications thereof have been found to capture the basic experimental phenomenology of bilayer-protein interactions in a wide range of experimental systems [4-11, 24-28, 31, 38-47, 81-83, 88-97], only involve parameters which can be measured directly in experiments, and are simple enough to allow analytic solutions. Analogous models have been formulated [7,48] to describe protein-induced curvature deformations [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and fluctuation-mediated interactions [49,[61][62][63][64][65][66][67][68]. In general, thickness-, curvature-, and fluctuation-mediated interactions all contribute to bilayer-mediated interactions between integral membrane proteins, but the relative strengths of these interactions depend on the specific experimental system under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…(3) and the corresponding "zeroth-order" models [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] capturing curvature-and fluctuation-mediated protein interactions absorb the molecular details of lipids and membrane proteins into effective material parameters. To provide a more detailed description of bilayer-protein interactions, a number of extensions and refinements of these models have been developed [44,45,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation